DARI KAPAL MENUJU MASYARAKAT - Refo, Ignasius SS. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2014)
The relationship between the ship and society in Nusantara has become the focus in recent years of many studies by archaeologists, historians, and anthropologists. The nature of this relationship is essential to the understanding of the traditional structure of the village and of the society. In very simplified terms the question posed boils down to the following: how can we explain the relation between the ship and the traditional society? How can we find the ideas of a ship in the governance structure of traditional society?